Data Privacy Issues, Young People, and the Use of Google Workspace for Education - visualise thesis (11382357) (2024)
Jennifer Grinham, Data Privacy Issues, Young People, and the Use of Google Workspace for Education Winner – The University of Sydney VYT local competition (2024) Educational technology product, Google Workspace for Education, is increasingly used in Australian high schools by students for learning. Commonly known as Google Classroom, its use accelerated during COVID-19 as part of supporting the ongoing provision of schooling during lockdowns. Google Workspace has now become a normal part of schooling in Australia and NSW. However, like other types of education technology, Google Workspace raises challenges for schools related to young people’s digital right to privacy that are currently poorly understood, especially from the viewpoint of students. This research aims to fill a gap in knowledge about the digital right to privacy by focusing on how students and schools perceive and respond to issues of data privacy when using Google Workspace for Education. It adopts a children’s rights framework and research methods include case studies of two secondary schools of differing socioeconomic advantage, surveys and interviews of key stakeholders, and document analysis, including of grey and white literature and legal and regulatory documents. Objectives include to analyse changes in data privacy issues for Australian high school students and compare these against different socioeconomic school profiles; understand perceptions and practices of data use and privacy by key school stakeholders in relation to Google Workspace for Education; understand changes as a response to COVID-19 and the effects of these on key stakeholders; and, to improve policy and governance responses to data privacy issues for students at Australian secondary schools.